Financial Ratio Analysis to Evaluate Financial Performance at PT Mayora Indah Tbk For The Period 2020-2023 - Ara, Alvarenza Willy; Sari, Maulina Rosyita; Claudia, Cindy (JSM: Jurnal Sains Manajemen, 2025)
The research paper examines the financial performance of PT Mayora Indah, Tbk from 2020 to 2023 through an analysis of liquidity, profitability, solvency, and activity ratios. Utilizing secondary data sources and descriptive statistical analysis, the study reveals that the company demonstrates good liquidity, profitability, and solvency, indicating effective management of assets and debts. The analysis includes discussions on the impact of the COVID-19 pandemic on PT Mayora Indah Tbk’s financial performance, market share, and various financial ratios. While the company excels in terms of the debt-to-equity ratio and working capital turnover, it shows fluctuations in fixed asset turnover and total asset turnover, suggesting areas for improvement in utilizing fixed assets and generating sales. Overall, PT Mayora Indah Tbk’s financial performance is deemed above average in working capital turnover but below average in fixed asset turnover and total asset turnover